PENGARUH DISIPLIN KERJA DAN KOMUNIKASI ORGANISASI TERHADAP OPTIMALISASI PELAYANAN DISTRIBUSI BERAS UNTUK MASYARAKAT MISKIN DI KECAMATAN BATUCEPER KOTA TANGERANG - Sampurna , Budi; Gustiana , Rachmat (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
This study aims to determine the "Effect of Work Discipline and Communication Services Organization against rice distribution to the poor in the district of Tangerang City Batuceper. For variable research is a discipline of work (X1), organizational communication (X2) and service distribution of rice for the poor employees (Y). The method used is quantitative method with associative kind that explains the relationship between independent variables and the dependent variable. Survey conducted on 102 employees in the district of Tangerang City Batuceper sampled from the total number of employees 115 people and literature as empirical studies support material. Hypothesis testing is done through the use of data processing package SPSS for Windows version 2013 statitisk correlation analysis method, determination coefficient and linear regression. As for the validity of the instrument is carried out through the test of validity, realibitas, normality and linearity data. Based on the analysis, the relationship of labor discipline (X1) with rice distribution services for the poor employees of rX1Y = 0.281 with a coefficient of determination (r2) of 0.079 with a regression equation Y = 56 180 + 0,263X1 while communication organization (X2) on rice distribution services for poor (Y) of rX2Y = 0.289 with a coefficient of determination (r2) of 0.83 with a regression equation Y = 57.217 + 0,248X2. The relationship between the discipline of work and communication organizations jointly positive effect of increasing the rice distribution services for the poor (Y) in the district of Kota Tangerangdengan Batuceper low leverage levels. This is evident from the results of calculation of correlation coefficient = 0.360 rX1X2Y that produce value determination coefficient of 0.1298, which means that the variation can be explained by the variable Y X1 for 12.98% and it is predicted through linear regression line equation y = 45.584 + 0,208X1 + 0,200X2. The conclusion of this study is evidence of the influence of labor discipline and organizational communication to service of distributing the rice to the poor clerk in Kecamatn Batuceper Tangerang City, so it is suggested the need for the application of the system of rewards and pusnihment, in order to consider the condition of the organization's communication of employees through their indicators, namely: the need for achievement, need for power and the need for affiliation, and to optimize the results of their research to be pursued further research, especially on variable epsilon